KEMAMPUAN MEMAHAMI PADANAN KATA BAHASA INDONESIA DI KALANGAN MAHASISWA IKIP SILIWANGI BANDUNG - Yenti Sulistian; Setya Susilawati; Ika Mustika (IKIP Siliwangi, 2018)
Globalization is often referred to as the era that has resulted from the entry of foreign cultural expression. The impact of globalization can affect life, including the language aspect. Facts show among young people including students who use more Indonesian language. Of course this should be wary if you do not want the Indonesian language